Talbragarus averyi gen. et sp. n., the first Jurassic weevil from the southern hemisphere (Coleoptera: Curculionoidea: Nemonychidae) - Oberprieler, Rolf G.; Oberprieler, Stefanie K. (Zootaxa, 2012)
The first authentic weevil fossils known from Australia, and the oldest known from the southern hemisphere, are describedand illustrated on the basis of two specimens recovered from the Upper-Jurassic Talbragar Fish Bed in New South Wales.Talbragarus averyi gen. et sp. n. is classified in the family Nemonychidae based on the presence of scutellary strioles onthe elytra, the length and insertion of the antennae and the shape of the eyes, prothorax, legs and overall body. Anassignment of Talbragarus to a subfamily of Nemonychidae is not possible due to the lack of preservation of crucialcharacters, but it may represent the subfamily Rhinorhynchinae, which is still extant in Australia. Talbragarus wasprobably associated with the dominant plant species found in the Talbragar Fish Bed, the araucariaceous Podozamitesjurassica, and may have fed on its pollen as adults and larvae as extant Australian Nemonychidae do, indicating that this insect-plant association may have survived in Australia from Jurassic times.